Vibroacoustics of complex structures - a wave chaos approach - Mohammed, Neekar Majeed (2021)
Modelling vibro-acoustics is of crucial importance in many areas of mechanical engineering and industry. In this PhD thesis we develop theoretical and computational methods for modeling vibro-acoustics of mechanical structures. We focus on simple structures such as flat plates and thin shells to investigate the vibro-acoustic response of structures using a phase-space method. These simple structures will provide quantitative guidance to the analysis of the vibroacoustics response of complex structures.